Integrated inspection of services for people with learning disabilities in Scotland: the way forward? - Campbell, Martin (Igitur, Utrecht Publishing & Archiving, 2007)
PURPOSE: The article summarises the process and the results of the first, integrated inspection of managed care services for people with learning disabilities in Scotland. The multi-agency model used was developed to be congruent with the existing performance inspection models, used by single agency inspection. The inspection activities and main outcomes are described, and suggestions are made for improvements. CONTEXT OF CASE: In 2006 an inspection model was devised to assess the quality of health, social services and education services for people with learning disabilities in one geographical area of Scotland, as a precursor to a programme of inspections nationally. The first joint, integrated inspection of all services for people with learning disabilities in Scotland took place in June 2006, and the report was published in March 2007. This was the first multi-agency inspection of its kind in the UK, and the first to involve carers and people with learning disabilities on the inspection team. DATA SOURCES: A number of data sources were used to check existing practice against agreed Quality Outcome indicators. Primary sources of data were social work records, health records, education records, staff surveys, carer surveys, interviews with staff, family carers and people with learning disabilities, and self evaluations completed by the services being inspected. Eleven different domains, each with sub-indicators were investigated. CASE DESCRIPTION: This paper summarises the process of an integrated, multi-agency inspection, how the inspection activities were conducted and the main findings of this inspection. Practical improvements to the process are suggested, and these may be of use to other services and inspectorates. CONCLUSIONS AND DISCUSSION: The integrated inspection was a qualified success. Most major objectives were achieved. The sharing of data amongst inspection agencies, establishing the level of commitment to integrated inspection and conducting multiple, integrated inspections nationally in a reasonable timescale are the main barriers remaining. The data were collected in an innovative way during this inspection, to make the analysis directly relevant to services, by providing domain specific and area specific details about how well local needs are being met. The lessons from this integrated inspection may be of interest to other practitioners in the UK and beyond, both in terms of process and outcomes.